2014
DOI: 10.1016/j.physa.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

From the time series to the complex networks: The parametric natural visibility graph

Abstract: We present the modification of natural visibility graph (NVG) algorithm used for the mapping of the time series to the complex networks (graphs). We propose the parametric natural visibility graph (PNVG) algorithm. The PNVG consists of NVG links, which satisfy an additional constraint determined by a newly introduced continuous parameter -the view angle. The alteration of view angle modifies the PNVG and its properties such as the average node degree, average link length of the graph as well as cluster quantit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 38 publications
(41 reference statements)
1
42
0
1
Order By: Relevance
“…The visibility graph was proposed by Bezsudnov [32] and used to transform the time series to graphs, then these graphs are regarded as vertices to construct a new network [33]. Here, we choose five timing points from t to t + 4 and set every timing point as one vertex in the network, if two elements (e.g., with height being the value of AQI) at different timing points are visible, they will be connected in the network (see Fig.…”
Section: A the Process And Properties Of Visibility Graphmentioning
confidence: 99%
“…The visibility graph was proposed by Bezsudnov [32] and used to transform the time series to graphs, then these graphs are regarded as vertices to construct a new network [33]. Here, we choose five timing points from t to t + 4 and set every timing point as one vertex in the network, if two elements (e.g., with height being the value of AQI) at different timing points are visible, they will be connected in the network (see Fig.…”
Section: A the Process And Properties Of Visibility Graphmentioning
confidence: 99%
“…cutoffs/thresholds) (Liu et al, 2015). VGs have been widely applied in many fields (Supriya et al, 2016;Stephen et al, 2015;Bezsudnov and Snarskii, 2014). However, as we discussed above, the VG has two disadvantages: first, it does not consider the effect of uneven sampling; second, it cannot capture the time series changes below a zero baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing industry in the application of complex network theory to carry out time series analysis [23,24]. The time series firstly is transformed into networks and then analyzed with various complex network tools [25][26][27][28]. Shirazi et al [29] demonstrated that the time series can be reconstructed with high precision by means of a simple random walk on their corresponding networks.…”
Section: Introductionmentioning
confidence: 99%